High‐Performance n‐Channel Thin‐Film Field‐Effect Transistors Based on a Nanowire‐Forming Polymer. (20th November 2012) - Hahm, Suk Gyu; Rho, Yecheol; Jung, Jungwoon; Kim, Se Hyun; Sajoto, Tissa; Kim, Felix S.; Barlow, Stephen; Park, Chan Eon; Jenekhe, Samson A.; Marder, Seth R.; Ree, Moonhor
Abstract A new electrontransport polymer, poly[N, N′‐dioctylperylene‐3, 4, 9, 10‐bis(dicarboximide)‐1, 7(6)‐diyl]‐alt‐[(2, 5‐bis(2‐ethyl‐hexyl)‐1, 4‐phenylene)bis(ethyn‐2, 1‐diyl] (PDIC8‐EB), is synthesized. In chloroform, the polymer undergoes self‐assembly, forming a nanowire suspension. The nanowire's optical and electrochemical properties, morphological structure, and field‐effect transistor (FET) characteristics are investigated. Thin films fabricated from a PDIC8‐EB nanowire suspension are composed of ordered nanowires and ordered and amorphous non‐nanowire phases, whereas films prepared from a homogeneous PDIC8‐EB solution consist of only the ordered and amorphous non‐nanowire phases. X‐ray scattering experiments suggest that in both nanowires and ordered phases, the PDIC8 units are laterally stacked in an edge‐on manner with respect to the film plane, with full interdigitation of the octyl chains, and with the polymer backbones preferentially oriented within the film plane. The ordering and orientations are significantly enhanced through thermal annealing at 200 °C under inert conditions. The polymer film with high degree of structural ordering and strong orientation yields a high electron mobility (0.10 ± 0.05 cm2 V−1 s−1), with a high on/off ratio (3.7 × 106), a low threshold voltage (8 V), and negligible hysteresis (0.5 V). This study demonstrates that the polymer in the nanowire suspension provides a suitable material for fabricating the active layers of high‐performance n‐channel FET devices via a solution coating process.